(untitled) (IAHS Medical Journal, 2024)
Background: This study discusses the issue of malnutrition among children under five in Bangladesh, particularly in the coastal areas where poverty and food insecurity are prevalent. Despite some progress, malnutrition remains a major cause of morbidity and mortality in these regions. Materials and methods: The study presents the results of a cross-sectional study that investigated the nutritional status of children under five and the significance of family income in relation to several socio-demographic aspects that could impact children’s nutritional condition. Results: The study found that 40.47% of the children were wasted, 42.85% were stunted, and 50% were underweight. The multivariate analysis found that the mother’s education, the socio-economic status of the family and the disease within the last 6 months had a significant association with the nutritional status of under 5 children. The study showed a significant correlation between a mother’s education and a child’s nutritional status, as well as household socioeconomic status. Conclusion: The research concludes that without taking precautions to address undernutrition and micronutrient deficiencies, human development is not possible and poverty, food insecurity, ignorance, a lack of proper feeding practices, infectious diseases, and poor hygiene and sanitation are the main factors contributing to high rates of maternal and child undernutrition in developing nations. IAHS Medical Journal Vol 6(1), June 2023; 44-46